Government Involvement on Tourism Policy and Programmes Implementation: A Case Study in Perhentian Island. - Zulkefli, Nor Syuhada; Jaafar, Mastura; Marzuki, Azizan (School of Social Sciences, USM, 2017)
The tourism sector has become vital for many developing countries including Malaysia. This sector has contributed to economic and social development of the country. Due to that, the government has given a special attention on the tourism sector development. Currently, there is a wide range of policies and programs to support the tourism sector. Thus, understanding the tourism policy and program implementation due to the multi-tiers government organization of Malaysia is important to be studied. Perhentian islands, is chosen as a case study. This study aims to explore the role of multi-tier of government and their engagement to implement tourism policy and programs. A qualitative case-study approach using the semi-structured interviews were applied to gain data onto sample of the three-tier government organizations who involve in the policy and program implementation. The main findings concluded that there was existing involvement and engagement process between the three-tiers of government organizations to implement the tourism policy and programs. Therefore, there is a clear need to delineate the responsibility of the three-tier organizations on the implementing of tourism policy and programmes in the Perhentian Islands.